Systemic Leadership and the Emergence of Ethical Responsiveness - Painter-Morland, Mollie (Journal of business ethics, 2008)
The author of this paper argues that the responsibility to nurture and encourage a relationally responsive ethical attitude among the members of an organizational system is shared by all who participate in it. In the dynamic environment of a complex adaptive organizational system where it is impossible to anticipate and legislate for every potential circumstantial contingency, creating and sustaining relationships of trust has to be a systemic capacity of the entire organization. Leadership is socially constructed, as the need for it arises within the complex interactions between individuals and groups within organizations, and can therefore not be described as a set of traits or behaviors possessed by only certain individuals who occupy positions of authority. If the sharing of this kind of relational responsiveness to the everyday realities of organizational life is to be properly understood, it is important to consider it in its concrete institutional manifestations. The last section of this paper therefore explores how an organization, in which leadership is understood in relational terms and is shared by all, looks and functions.